Schmerzassessment bei älteren Menschen in der vollstationären Altenhilfe: Methodenpapier zur S3-Leitlinie - Sirsch, Erika; Berkemer, Esther (Der Schmerz, 2012)
In Germany, there is currently no guideline for pain assessment in elderly people. Pain management in nursing home residents is, however, legally required. For this particular group, especially for people with dementia, suitable interdisciplinary orientations for health care are lacking in Germany. The working group “Pain and Age” of the German Pain Society (“Deutschen Schmerzgesellschaft”) in conjunction with the German Centre for Neurodegenerative Diseases (“Deutschen Zentrum für Neurodegenerative Erkrankungen”), Witten, has embarked on the development of interdisciplinary S3-Guideline for “Pain Assessment in Elderly People in Nursing Homes”, based on the methodology suggested by the Association of the Scientific Medical Societies (“Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften e. V.”), the German Agency for Quality in Medicine (“Ärztliche Zentrum für Qualität in der Medizin”), and that described in the DELBI (“Deutschen Leitlinien-Bewertungsinstrument”). Delegates of the 38 scientific societies and interest groups currently participating can contribute to the contents on three different levels. The present article outlines the methods for developing the guideline.
Gesehen am 12.08.2019